Diseño de un manual de funciones por competencias para la gestión del talento humano de la Empresa Pública ESPAM MFL–EP - Vera Sabando, Josselyne Sofía (2023)
The purpose of this work is to contribute to the management of public servants who work in the Public Company ESPAM MFL-EP from the identification of suitable skills for their job profiles. This is a qualitative, descriptive, which was supported by the analytical - synthetic and inductive-deductive methods. The collection of information was done through the analysis of documents and the interview. The procedure used consisted of three phases, in the first phase the skills, competencies, level of complexity and responsibility that each position implies according to its hierarchy in the occupational structure were analyzed through the evaluation and classification of positions, for the second phase They defined the functions of the employees according to the position they carry out through the analysis of positions and finally a manual of functions was proposed for the development and strengthening of the management of human talent by competences of the ESPAM MFL - EP. Among the most relevant results is the assignment of technical behavioral competencies to each professional profile, the detection of the activities of the position that are essential with their respective prioritization, the assessment of the activities of the positions together with the respective classification by occupational group, in addition to the representation of the hierarchical and communicational organic structure. Finally, it is concluded that the skills, competencies, functions of the non-professional, professional and managerial positions existing in the institution are adequate to the hierarchical level to which they belong, comply with the current legal system and promote adequate performance of human talent.